2018
DOI: 10.1513/annalsats.201804-241oc
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Intensive Care Unit Capacity Strain with Disposition and Outcomes of Patients with Sepsis Presenting to the Emergency Department

Abstract: The odds that patients in the ED with sepsis who do not require life support therapies will be admitted to the ICU are reduced when those ICUs experience high occupancy but not high levels of other previously explored measures of capacity strain. Patients with sepsis admitted to the wards during times of high ICU occupancy had increased odds of hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…Routine variations in capacity strain alter care processes and some clinical outcomes in the emergency department, hospital wards, and intensive care unit (ICU) (2)(3)(4)(5)(6)(7)(8)(9). However, pandemic-induced strains on capacity far exceed levels observed during peaks in routine demand, requiring new frameworks to guide hospital investments in and allocations of resources to prevent grave consequences of strain.…”
mentioning
confidence: 99%
“…Routine variations in capacity strain alter care processes and some clinical outcomes in the emergency department, hospital wards, and intensive care unit (ICU) (2)(3)(4)(5)(6)(7)(8)(9). However, pandemic-induced strains on capacity far exceed levels observed during peaks in routine demand, requiring new frameworks to guide hospital investments in and allocations of resources to prevent grave consequences of strain.…”
mentioning
confidence: 99%
“…This finding was robust in multiple sensitivity analyses and after adjustment for patient characteristics as well as other ''strain'' variables, such as intensive care unit turnover, intensive care unit daily census and ward occupancy [29]. The authors interpreted this to mean that a 10% increase in intensive care unit occupancy was associated with a 13% decrease in the odds of admission to the intensive care unit [29].…”
Section: Factors Influencing Patient Triage Decisionsmentioning
confidence: 82%
“…However, in a prospective observational study in France by Robert et al [32], the authors found that patients admitted to the intensive care unit after being initially refused admission due to capacity constraints had higher 28-day and 60-day mortality [32]. Similarly, Anesi et al found that patients with sepsis admitted to the general ward from the emergency department during times of higher intensive care unit occupancy had higher odds of in-hospital mortality (odds ratio 1.61, 95% confidence interval 1.21-2.14) [29]. The results from both of these studies strongly suggest that not only are triage decisions influenced by capacity, but patient outcomes may suffer as a downstream consequence of denying access to the intensive care unit.…”
Section: Association Between Intensive Care Unit Bed Supply and Patiementioning
confidence: 98%
See 2 more Smart Citations